Cuidados na velhice, no adoecimento e na morte: relatos e reflexões sobre a finitude como forma de investimento na vida - Costa, Debora Cristina Genezini (2011)
To be born, grow up, develop, reproduce, get old and die: this is the possible image of the human life cycle. Even though definite and natural, age and the end of life seem to haunt humans. As a result of the stereotypy and denial of old age and death, assistance to the sick elderly easily follows distorted ways. Healthcare assistance, as a reflex of the technicalities and the biopower focuses the cure and life sustaining by means of the excessive use of technological resources. The voice of the elderly expressing autonomy and their wishes is frequently damped down by medical procedures, and the boundaries between life and death seem to separate and antagonize. Considering this, the contents of this work show some snapshots regarding the old age and death among new paradigms for and against the elderly care in sickness and at the end of life. General media documents and articles, movies, and theorists will be some of the interlocutors. In the same way, the voices from elderly, family members, and healthcare professionals will bring insights about how to look into, plan and care for the old age. Gerontology, Palliative Care, and the Living Will proposition are presented as potentially facilitating agents in the planning and assistance for the sick elderly